Forecasting real economic activity and inflation : the role of geopolitical risks and economic policy uncertainty in major economies - Hundal, Amaya (2023)
The increasing prominence of geopolitical risks and economic policy uncertainties globally has brought their impacts on overall economies to the forefront in both academia and policymaking. Current literature, while being rich in focus on economic policy uncertainty, represented by the EPU index, and financial and macroeconomic variables, is limited in research exploring the dynamics of geopolitical risks, represented by the GPR index, and is even more so limited in research offering a comparison of the two indices in terms of their forecasting content for real economic activity and inflation. This thesis focuses on the interactions between the global GPR index, the global EPU index, 3-month money market interest rate, term spread, dividend yield, real economic activity, and inflation, for Germany, the UK, and the US, through a VAR analysis whereby causal relationships and dynamic interactions are brought to the forefront. Furthermore, rolling out-of-sample forecasts for real economic activity and inflation are conducted based on models of conventional financial market variables and models augmented with the GPR and EPU indices in addition to the conventional variables. Results indicate causality between the EPU index and the macroeconomy to flow through the financial market variables with no significant causal relationships found with the GPR index. Significant relationships are found between the EPU index, and dividend yield, 3-month money market interest rate, and term spread of all three countries, as well as between the EPU index and real economic activity of Germany and the US, by Granger causality tests, impulse response functions, and variance decompositions. The VAR-based forecasts, however, indicate the superiority of the model augmented with the GPR index in addition to conventional financial market variables, given by a small margin, in yielding accurate forecasts of real economic activity for Germany, the UK, and the US, over that of conventional financial market variables and the models inclusive of the EPU index. Thus, the importance of understanding the dynamic interactions between economic policy uncertainty, the financial markets, and the economy is highlighted, and the relevance of geopolitical risks is emphasised in forecasting future real economic activity.